2005
DOI: 10.2320/matertrans.46.130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Internal Structure on Thermal Properties of Alumina/Aluminum Composites Fabricated by Gelate-Freezing and Partial-Sintering Process, Respectively

Abstract: The purpose of the present work was to clarify the effects of parameters of porous ceramics on the characteristics of composites fabricated by high-pressure infiltration. Alumina with different porosity (15-70 vol%) and pore morphology was successfully fabricated by gelate-freezing and the partial-sintering, respectively. Alumina/aluminum composites were made by squeeze casting, the aluminum into the alumina sintered bodies. By evaluating the coefficient of thermal expansion (CTE) and thermal conductivity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Table 5 lists the thermal expansion coefficients (TEC) of specimens obtained from formulations S1 and S2, measured by the tangent of the curve at temperature intervals between 25 and 1000ºC. Between 25 and 1000ºC, the TEC values lie within the range of 6.2 to 6.9 x 10 -6°C-1 , which may be ascribed to the presence of crystalline phases (Table 2), mainly mullite and corundum, which present TEC of ~ 5 to 6 x 10 -6°C-1 and ~ 7 to 8 x 10 -6°C-1 , respectively [44][45][46][47] . These values are close to those reported by Chen et al 48 , who analyzed the TEC of corundum-mullite composites and found that samples with higher levels of alumina (Al 2 O 3 ) showed higher values of TEC 200-1100 of ~ 6 to 7 x 10 -6 K -1 .…”
Section: Resultsmentioning
confidence: 94%
“…Table 5 lists the thermal expansion coefficients (TEC) of specimens obtained from formulations S1 and S2, measured by the tangent of the curve at temperature intervals between 25 and 1000ºC. Between 25 and 1000ºC, the TEC values lie within the range of 6.2 to 6.9 x 10 -6°C-1 , which may be ascribed to the presence of crystalline phases (Table 2), mainly mullite and corundum, which present TEC of ~ 5 to 6 x 10 -6°C-1 and ~ 7 to 8 x 10 -6°C-1 , respectively [44][45][46][47] . These values are close to those reported by Chen et al 48 , who analyzed the TEC of corundum-mullite composites and found that samples with higher levels of alumina (Al 2 O 3 ) showed higher values of TEC 200-1100 of ~ 6 to 7 x 10 -6 K -1 .…”
Section: Resultsmentioning
confidence: 94%
“…In most cases, such composites are made, using an isotropic [22] preforms, but some papers have reported composites prepared from freeze casted ones [23,24]. For example, Roy et al [14] have filled porous alumina preforms with an aluminium alloy and they studied the elastic behaviour of such composites.…”
Section: Introductionmentioning
confidence: 98%